Numerical investigation of the joint impact of thermophoresis and radiative losses in induction plasma synthesis of copper nanoparticles. (22nd March 2017) - Bianconi, S; Boselli, M; Gherardi, M; Colombo, V
Abstract: A numerical model for the simulation of the copper nanoparticles synthesis process by an induction thermal plasma system has been developed, taking into account the joint effects of radiative losses from the metallic vapour and thermophoretic transport of the synthetized nanoparticles on the process performance; the final aim of the work is that of setting up an accurate modelling tool for design-oriented simulation and optimization of the synthesis process. Radiative losses from copper vapour and thermophoresis have been taken into account for different reaction chamber geometries (a cylindrical one and one with a conical top section) combined with different quench gas injection strategies and different power levels, in order to evaluate the impact of these phenomena in process design strategies. The numerical results show that both these phenomena have a relevant impact on the process parameters for all the investigated cases, and that they should be taken into account in order to develop increasingly accurate models for process design and optimization.